The inotropic and arrhythmogenic effects of acutely increased late INa are associated with elevated ROS but not oxidation of PKARIα - Gissibl, Theresa; Stengel, Laura; Tarnowski, Daniel; Maier, Lars S.; Wagner, Stefan; Feder, Anna-Lena; Sag, Can Martin (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute stimulation of the late sodium current (INaL) as pharmacologically induced by Anemonia toxin II (ATX-II) results in Na+-dependent Ca2+-overload and augmentation of reactive oxygen species (ROS), accompanied by an increase in the amplitude of the systolic Ca2+ transient. Ca2+ transient amplitude is determined by L-type Ca2+-mediated transsarcolemmal Ca2+-influx (ICa) into the cytosol and by systolic Ca2+-release from the sarcoplasmic reticulum (SR). Increased ROS activates Type-1 protein kinase A (PKARI) and is capable of stimulating ICa, thereby sustaining the amplitude of the systolic Ca2+ transient upon oxidative stress. Objectives: We aimed to investigate whether the increase of the systolic Ca2+ transient as acutely induced by INaL (by ATX-II) may involve stimulation of ICa through oxidized PKARI Methods: We used a transgenic mouse model in which PKARI was made resistant to oxidative activation by homozygous knock-in replacement of redox-sensitive cysteine 17 with serine within the regulatory subunits of PKARI (KI). ATX-II (at 1 nmol/L) was used to acutely enhance INaL in freshly isolated ventricular myocytes from KI and wildtype (WT) control mice. Epifluorescence and confocal imaging were used to assess intracellular Ca2+ handling and ROS formation. Ruptured-patch whole-cell voltage-clamp was used to measure INaL and ICa. The impact of acutely enhanced INaL on RIα dimer formation and PKA target structures was studied by Western blot analysis. Results: ATX-II increased INaL to a similar extent in KI and WT cells, which was associated with significant cytosolic and mitochondrial ROS formation in both genotypes. Acutely activated Ca2+-handling in terms of increased Ca2+ transient amplitudes and elevated SR Ca2+ load was equally present in KI and WT cells. Likewise, cellular arrhythmias as approximated by non-triggered Ca2+ elevations during Ca2+ transient decay and by diastolic SR Ca2+-spark frequency occurred comparably in both genotypes. Most importantly and in contrast to our initial hypothesis, ATX-II neither altered the magnitude or inactivation kinetics of ICa in WT nor KI cells and did not result in PKARI dimerization (i.e. oxidation) despite a clear pro-oxidant intracellular environment. Conclusions: The inotropic and arrhythmogenic effect of acutely increased INaL is associated with elevated ROS, but does not involve oxidation of PKARI